Chia protein hydrolysates: characterisation and emulsifying properties - Salazar Vega, Ine M. (2021)
The evaluation of functional properties of different chia protein hydrolysates (CPH) and their application in O/W emulsions were studied. Enzymatic treatments with pepsin, pancreatin or the sequential action of pepsin–pancreatin were applied to hydrolyse a chia protein concentrate (CPC). Oil-in-water emulsions stabilised with CPC or these CPHs, with or without chia mucilage, were prepared at pH 7 or 10. Particle size, global stability, ζ-potential and rheological measurement of emulsions were determined. CPH presented higher (P ≤ 0.05) solubility and surface hydrophobicity levels, exhibiting better emulsifying properties than CPC. Emulsions with CPH presented smaller (P ≤ 0.05) droplet sizes than those with CPC. Regarding to physicochemical stability, emulsions at pH 7 were less stable than those at pH 10, showing destabilisation by creaming and coalescence. The addition of chia mucilage increased the apparent viscosity of emulsions and led to modifications in their fluid behaviour, exhibiting an interesting role as a thickening agent.